2021
DOI: 10.3390/ijms22052772
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of Novel 3-Carboranyl-1,8-Naphthalimide Derivatives as Potential Anticancer Agents

Abstract: We synthesized a series of novel 3-carboranyl-1,8-naphthalimide derivatives, mitonafide and pinafide analogs, using click chemistry, reductive amination and amidation reactions and investigated their in vitro effects on cytotoxicity, cell death, cell cycle, and the production of reactive oxygen species in a HepG2 cancer cell line. The analyses showed that modified naphthalic anhydrides and naphthalimides bearing ortho- or meta-carboranes exhibited diversified activity. Naphthalimides were more cytotoxic than n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 85 publications
4
32
0
Order By: Relevance
“…ROS accumulation could damage DNA directly and cause oxidative lesions; 8-oxo-dG could be a reliable biomarker of OS [42]. Under normal conditions, a genome has one 8-oxo-dG molecule per 10 5 -10 6 guanosines, which is equivalent to thousands of 8-oxo-dG molecules per cell [102]. We found that all the tested compounds significantly elevated the number of 8-oxo-dG molecules as compared to control cells; this finding complements the above considerations and confirms that both the adenosine derivatives induce OS in T98G cells (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…ROS accumulation could damage DNA directly and cause oxidative lesions; 8-oxo-dG could be a reliable biomarker of OS [42]. Under normal conditions, a genome has one 8-oxo-dG molecule per 10 5 -10 6 guanosines, which is equivalent to thousands of 8-oxo-dG molecules per cell [102]. We found that all the tested compounds significantly elevated the number of 8-oxo-dG molecules as compared to control cells; this finding complements the above considerations and confirms that both the adenosine derivatives induce OS in T98G cells (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…As reported earlier, the introduction of boron clusters into drug molecules could improve the activity toward resistant forms [16][17][18][19] or to obtain hitherto unknown nematicidal activity [20]. Structures of mitonafide, pinafide, and 1,8-naphthalimides modified with a carborane cluster [8,9].…”
Section: Introductionmentioning
confidence: 90%
“…In our work, we have described thus far the methods used to synthesize naphthalimides modified with carborane or metallacarborane groups through the modification of imide (Figure 1) [8] and bearing the carborane group at position 3 of the ring [9]. We observed that the attachment site of the boron cluster to the naphthalimide moiety, type of the boron cluster, and structure of the linker between the boron cluster and the heteroaromatic ring system influenced various cytotoxic activities against HepG2 cancer cells.…”
Section: Introductionmentioning
confidence: 91%
“…In boron neutron capture therapy (BNCT), the first step is the selective accumulation of 10 B-containing compounds in cancer cells, which can be irradiated by low-energy and harmless thermal neutrons. 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Subsequently, 10 B atoms break up into α particles and lithium nuclei, yielding high linear energy transfer (LET) particles ( Figure 2 ). 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 As a result, 10 B-containing cancer cells can be destroyed by the high-LET particles.…”
Section: Applications Of Carboranes As Boron Neutron Capture Therapy Agentsmentioning
confidence: 99%
“… 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 Subsequently, 10 B atoms break up into α particles and lithium nuclei, yielding high linear energy transfer (LET) particles ( Figure 2 ). 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 As a result, 10 B-containing cancer cells can be destroyed by the high-LET particles. In contrast, the surrounding normal/healthy cells can survive because of the limited path length of these particles of only 5–9 μm, which is smaller than the diameter of a general cell.…”
Section: Applications Of Carboranes As Boron Neutron Capture Therapy Agentsmentioning
confidence: 99%